Elimination profiles of prednisone and prednisolone after different administration routes: Evaluation of the reporting level and washout periods to ensure safe therapeutic administrations. Issue 3 (20th November 2020) - Coll, Sergi; Monfort, Núria; Alechaga, Élida; Matabosch, Xavier; Pozo, Oscar J.; Pérez‐Mañá, Clara; Ventura, Rosa
Abstract: Prednisolone (PRED) and prednisone (PSONE) are prohibited in sports competitions when administered by systemic routes, and they are allowed by other routes for therapeutic purposes. There is no restriction of use in out‐of‐competition periods. The present study aimed to evaluate the urinary excretion of PRED, PSONE, and their most important metabolites after systemic and nonsystemic treatments in order to verify the suitability of the current reporting level of 30 ng/ml used to distinguish allowed and prohibited administrations and to establish washout periods for oral treatments performed in out‐of‐competition periods. PRED was studied after dermatological administration (5 mg/day for 5 days, n = 6 males) and oral administration (5 mg, n = 6 males; 10 mg, n = 2 males). PSONE was studied after oral administration (10 mg, n = 2 males; 30 mg, n = 1 male and 1 female). Concentrations in urine were measured using an LC–MS/MS method. Concentrations after dermatological treatment were low for all metabolites. After oral administration, concentrations were very high during the first 24 h after administration ranging from 1.6 to 2261 ng/ml and from 4.6 to 908 ng/ml for PRED and PSONE, respectively. Concentrations of most of the metabolites measured were lower than 30 ng/ml from 24 h after all oral administrations. New reporting levels are proposed for PRED and PSONE considering data of our study and other information published after nonsystemic administrations of the compounds. Washout periods of at least 24 h are recommended to ensure no false positives when oral treatments need to be performed in out‐of‐competition periods. Abstract : The urinary excretion profiles of prednisolone, prednisone, and four metabolites were evaluated after systemic and nonsystemic administrations. New reporting levels are proposed to discriminate between allowed and prohibited administrations of prednisone and prednisolone in sports. A washout period of at least 24 h is proposed for oral treatments with these glucocorticoids.